Tiếp cận với việc lập trình gia công trên máy CNC - Tăng, Huy (Bộ Giáo dục và Đào tạo, 2013)
Automation of production equipment is making ever-increasing demands in manufacturing engineering. Progress has been, made in CNC systems due to message exchange capabilities, graphic support and tool handling. This article is intendes to present program preparation methods to modern CNC technology.